Foreign ownership and bribery: Agency and institutional perspectives. Issue 1 (February 2018) - Yi, Jingtao; Teng, Da; Meng, Shuang
Highlights: Foreign ownership exacerbates bribery intensity due to the agency problem between the headquarter and its foreign subsidiaries. Formal institutions negatively moderate the positive relationship between foreign ownership and bribery intensity. We show the substitute effects of formal institutions and external auditing in controlling this unethical activity. Abstract: In this study we examine the effectiveness of formal institutions (as the macro-level mechanism) and external auditing (as the micro-level mechanism) in controlling multinational firms' engagement in bribery. We adopt World Bank's data and investigate 38, 673 firms in 113 countries. Our results suggest that a firm's engagement in bribery is positively related to its foreign ownership. Furthermore, we demonstrate the substitute effects of formal institutions and external auditing in controlling this unethical activity. We argue that in a situation whereby formal institutions are weak, a firm's internal governance mechanism plays a vital role in controlling bribery.